Effect of Porosity on the Thermo-Mechanical Behavior of Friction-Stir-Welded Spark-Plasma-Sintered Aluminum Matrix Composites with Bimodal Micro- and Nano-Sized Reinforcing Al2O3 Particles - Behzad Sadeghi; Behzad Sadeghian; Aboozar Taherizadeh; Aleksandra Laska; Pasquale Cavaliere; Arun Gopinathan (Metals, 2022)
The thermo-mechanical behavior of nanosized Al2O3 particles reinforcing aluminum was analyzed in the present paper. The material was prepared by spark plasma sintering and friction stir welding. The thermal stresses affecting the composite behavior during welding were modeled through COMSOL MultiPhysics, and the results were validated by the analyses of the composites’ mechanical properties. The spark-plasma-sintered materials presented limited porosity, which was taken into account during the modeling phase. Both model and experiments revealed that higher heat input is related to better material mixing during welding and sound mechanical properties. Thermal stresses lead to residual stresses close to 300 MPa in the thermo-mechanically affected zone for processing conditions of 1900 RPM and 37 mm/min. This leads to an increase in hardness up to 72 HV.